Fluvial flood risk in Europe in present and future climates - Feyen, Luc; Dankers, Rutger; Bódis, Katalin; Salamon, Peter; Barredo, José I. (Climatic change, 2012)
In this work we evaluate the implications of climate change for future fluvial flood risk in Europe, considering climate developments under the SRES A2 (high emission) and B2 (low emission) scenario. We define flood risk as the product of flood probability (or hazard), exposure of capital and population, and vulnerability to the effect of flooding. From the European flood hazard simulations of Dankers and Feyen (J Geophys Res 114:D16108. doi: 10.1029/2008JD011523 , 2009 ) discharges with return periods of 2, 5, 10, 20, 50, 100, 250 and 500 years were extracted and converted into flood inundation extents and depths using a planar approximation approach. Flood inundation extents and depths were transformed into direct monetary damage using country specific flood depth-damage functions and land use information. Population exposure was assessed by overlaying the flood inundation information with data on population density. By linearly interpolating damages and population exposed between the different return periods, we constructed damage and population exposure probability functions under present and future climate. From the latter expected annual damages (EAD) and expected annual population exposed (EAP) were calculated. To account for flood protection the damage and population exposure probability functions were truncated at design return periods based on the country GDP/capita. Results indicate that flood damages are projected to rise across much of Western Europe. Decreases in flood damage are consistently projected for north-eastern parts of Europe. For EU27 as a whole, current EAD of approximately €6.4 billion is projected to amount to €14–21.5 billion (in constant prices of 2006) by the end of this century, depending on the scenario. The number of people affected by flooding is projected to rise by approximately 250,000 to 400,000. Notwithstanding these numbers are subject to uncertainty, they provide an indication of potential future developments in flood risk in a changing climate.